Diet and Sleep Physiology: Public Health and Clinical Implications - Frank, Sarah; Gonzalez, Kelli; Lee-Ang, Lorraine; Young, Marielle C.; Tamez, Martha; Mattei, Josiemer (Frontiers in Neurology, 2017)
This mini review examines the complex relationship between diet and sleep, and explores the clinical and public health implications of the current evidence. Dietary quality and intake of specific nutrients can impact regulatory hormonal pathways to alter sleep quantity and quality. Sleep, in turn, affects the intake of total energy, as well as of specific foods and nutrients, through biological and behavioral mechanisms. Initial research in this field focused primarily on the effects of short sleep duration on nutritional quality. However, more recent studies have explored the dynamic relationship between long sleep duration and diet. Current evidence suggests that extremes of sleep duration alter sleep patterns, hormonal levels, and circadian rhythms, which contribute to weight-related outcomes and obesity, and other risk factors for the development of chronic disease such as type 2 diabetes and cardiovascular disease. These patterns may begin as early as childhood and have impacts throughout the life-course. Given that non-communicable diseases are among the leading causes of death globally, deeper understanding of the interactions between sleep and nutrition has implications for both public health and clinical practice.